Orobanche dominae (Orobanchaceae), a new species described from Tunisia, North Africa - El Mokni, Ridha (Mediterranean Botany, 2023)
Orobanche dominae El Mokni (section Orobanche L.) is described and illustrated as a new species to science, endemic to central-eastern Tunisia, North Africa. The new species is known only from a single population within olive groves of Mahdia area, where it grows on sandy loam soil and parasiting on the Tuniso-Libyan endemic Onopordum espinae Bonnet. It is a medium almost brownish-purple plant characterized by a precocious and very short blooming period. It has a cylindrical, long inflorescence with erecto-patent and long sized flowers. The corolla exhibits varying colors along with short and long glandular hairs in addition to an almost glabrous style on the lower part. The macromorphological features suggest a closer relationship of this new species to the members of the subsections Minores Teryokhin and Speciosae Novopokr., in particular with Or. crenata Forssk., Or. minor Sm., and Or. artemisiae-campestris Gaudin s.l. (so far the only known Orobanche that was mentioned parasitizing one of the Onopordum species, On. illyricum L.). Relationships and discriminating morphological features of the new species with its closest species are examined. Data on its ecological and conservation status together with its main host(s) and distributive area are also presented.